2018
DOI: 10.2331/suisan.17-00025
|View full text |Cite
|
Sign up to set email alerts
|

Observations of gut contents of anguilliform leptocephali collected in the western North Pacific

Abstract: The gut contents of anguilliform leptocephali collected by research cruises in the western North Paciˆc were examined in order to investigate their food sources. Gut contents of 26 leptocephali (Anguillidae, Congridae and Serrivomeridae) examined were amorphous food material containing many small spherical particles. Alcian Blue (AB)-stained aggregates containing spherical particles approximately 2 10 mm in diameter were observed in 14 leptocephali from the 2015 survey, and Coomassie Brilliant Blue (CBB)-stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“…This assumption is consistent with the low trophic position of the eel leptocephali (Otake et al, 1993;Kimura and Tsukamoto, 2006;Chow et al, 2010;Miyazaki et al, 2011;Miller et al, 2013) and the feeding apparatus constrained to feed on small and/or soft particle (Bouilliart et al, 2015). Since the nets (CMS and MS) used in the present study were 60 and 30 mm in mesh size, the aggregates and small spherical POMs reported by Tomoda et al (2017) were not adequately collected and supplied to the leptocephali during the experiments in this study. Development of a method to collect large amount of seawater together with such fine particles and soft aggregates is necessary to elucidate the efficacy of the small POMs as the feed for the Japanese eel leptocephali.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…This assumption is consistent with the low trophic position of the eel leptocephali (Otake et al, 1993;Kimura and Tsukamoto, 2006;Chow et al, 2010;Miyazaki et al, 2011;Miller et al, 2013) and the feeding apparatus constrained to feed on small and/or soft particle (Bouilliart et al, 2015). Since the nets (CMS and MS) used in the present study were 60 and 30 mm in mesh size, the aggregates and small spherical POMs reported by Tomoda et al (2017) were not adequately collected and supplied to the leptocephali during the experiments in this study. Development of a method to collect large amount of seawater together with such fine particles and soft aggregates is necessary to elucidate the efficacy of the small POMs as the feed for the Japanese eel leptocephali.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, Tomoda et al (2017) found that Alcian-blue stained aggregates (polysaccharides), Coomassie-brilliantblue stained aggregates (proteins) and small spherical particle (2-10 mm in diameter) were common between the environmental water and the gut contents of anguilliform leptocephali, suggesting POM originated from phytoplankton and cyanobacteria to be food sources for the leptocephali. This assumption is consistent with the low trophic position of the eel leptocephali (Otake et al, 1993;Kimura and Tsukamoto, 2006;Chow et al, 2010;Miyazaki et al, 2011;Miller et al, 2013) and the feeding apparatus constrained to feed on small and/or soft particle (Bouilliart et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations